Effect of planting date on severity of frogeye leaf spot and grain yield of soybeans - Akem, C.; Dashiell, Kenton E. (Elsevier, 1994)
The influence of soybean (Glycine max) planting date on seasonal epidemics of frogeye leaf spot caused by Cercospora sojina and on grain yield, was evaluated during the 1991 and 1992 cropping seasons. Two susceptible (Samsoy 1 and TGx 849-313D) and one resistant (TGx 996-26E) soybean cultivars were used in field trials at Zonkwa, in the southern Kaduna state of Nigeria. Four field plantings were made at 14-day intervals from late May to mid0July. For each planting date, half the plots received foliar applications of benomyl at R1 and R3 growth stages, and the other half was untreated. Frogeye disease severity ratings were taken for all plots at R4 to R5 growth stages, and grain yield for each plot was measured at harvest. There was a significant (p < 0.05) increase in disease severity between the first and third plantings on the two susceptible cultivars in 1991, and on TGx 849-313D only in 1992. Corresponding yield reductions for the two susceptible cultivars averaged 13 and 31% for the treated and untreated plots, respectively, with each 2-week delay beyond the first planting date in 1991, and 5 and 6%, respectively, in 1992. There was no significant difference in disease among all treatments on the resistant cultivar, TGx 996-26E. Under Nigerian conditions, an increase in frogeye leaf spot severity can be expected with delayed planting of soybean after 1 June, and this can result in a corresponding loss of crop yield.